Mapping varieties of industrial relations: Eurofound’s analytical framework applied - Caprile, Maria; Sanz, Pablo; Riobáo, Irene; Welz, Christian; Rodrigues, Ricardo (Luxembourg, 2018)
"Eurofound’s 2016 report Mapping key dimensions of industrial relations identified four key dimensions of industrial relations: industrial democracy, industrial competitiveness, social justice, and quality of work and employment. This report builds upon that earlier study, developing a dashboard of 45 indicators to assess how and to what extent the conceptual framework of these key dimensions can be applied at national level. The indicators were tested across the Member States by Eurofound’s Network of European Correspondents and show reasonable accuracy when used to map the predominant features and trends of the national industrial relations systems. The study confirms that a dashboard of indicators that can accurately measure and summarise the complex reality of industrial relations across the EU is a valuable tool for comparative research and a useful instrument for supporting policymakers, social partners and stakeholders. The report sets out a range of options for further developing this conceptual approach."